Assessing anti-racist resources online: Developing a framework for examining institutions’ online anti-racist outreach and engagement - Nutt, Rachael; Gray, LaVerne (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
Examining the response of a library during a tumultuous period not only provides insight about the library’s past, but also allows the library to improve its actions to better serve its communities in the future. The summer of 2020 marked such a period in American history. Amidst the cries for systemic change following the murder of George Floyd, the social media profiles of individuals and organizations alike–including academic libraries–flooded with anti-racist reading lists, informational articles, webinars, and other such educational materials. How do we qualify these resources? How do we understand the roles that academic libraries play in this resource sharing, and how do we use that information to assess their involvement? Building upon Dr. Bharat Mehra and Dr. Rebecca Davis’ (2015) Strategic Diversity Manifesto, this talk describes the beginning of a project meant to determine how academic libraries can examine their online presences: where and how they have raised their voices, incorporated the voices of others, or stayed silent.